Validation and the role of PDK4 relevant to ferroptosis in degenerative lumbar disc disease - Wenhao Chen; Wanliang Yang; Bin Meng; Xingkun Wang; Heng Duan; Qian Xu; Hao Li (Journal of Orthopaedic Surgery and Research)
Abstract Background Ferroptosis was involved in the pathogenesis of intervertebral disc degeneration (IVDD). However, the exact mechanism of IVDD associated with ferroptosis still required deeper studies. Method The differentially expressed genes (DEGs) in rat lumbar disc tissue between the control and IVDD group treated with IL-1β were detected by RNA sequencing (RNA-seq). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were performed on DEGs. We further screened the differential expressed ferroptosis-related genes (DEFRGs). Besides, a protein-protein interaction (PPI) network of DEFRGs was constructed by STRING database. The Cytoscape database identified significant modules and the hub genes. The loss function of PDK4 by siRNA inference was investigated in NPCs by CCK8 assay, ELISA assay, and the analysis of ferroptosis indicators. Result DEGs were identified using RNA-seq. KEGG pathway analysis showed that these genes were mainly involved in Parkinson’s disease, oxytocin signaling pathway, calcium ion signaling pathway, AMPK signaling pathway, and glucagon signaling pathway. Eight hub genes (including LDHA, PKM, EP300, EGFR, EGLN1, SCD, PDK4, and FABP4) were found by the PPI network and Cytoscape on a total of 25 ferroptosis-related genes that were identified in rat lumbar disc tissue after IVDD treatment. PDK4 silencing promoted NPCS proliferation, decreased the levels of the proinflammatory factors, and suppressed ferroptosis. Conclusion The study suggested the potential roles of ferroptosis-related genes in IVDD and further revealed the role of PDK4 in the progression of IVDD.